Manajemen Disfungsi Otonom Terbaru pada Penyakit Parkinson - Nugraha, Priya; Puspamaniar, Vania Ayu (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2025)
Since James Parkinson's 1817 initial description of Parkinson's disease (PD), autonomic dysfunction has been identified in PD patients. Parkinson disease (PD) is clinically heterogeneous due to motor and nonmotor symptoms, disease progression, and treatment responses. Autonomic dysfunction can cause a variety of symptoms, such as gastrointestinal, cardiovascular, urogenital, thermoregulatory, irregular pupillary movements, respiratory, and sleep symptoms. The idea that autonomic dysfunction may have a major role in PD patients' mobility, cognition, and health-related quality of life (HRQoL) is supported by several studies. Current management, as determined by the most recent guidelines, is crucial for updating physician expertise. Appropriate care is contingent upon a correct and timely diagnosis which will enhance the quality of life for PD patients. A thorough discussion of the clinical symptoms and current therapy will be provided in this article.